Clinical Implications of Basic Science Discoveries: Janus Resurrected—Two Faces of B Cell and Plasma Cell Biology. Issue 1 (7th November 2014) - Woodle, E. S.; Rothstein, D. M.
<x xml:space="preserve">Abstract</x> B cells play a complex role in the immune response. In addition to giving rise to plasma cells (PCs) and promoting T cell responses via antigen presentation, they perform immunoregulatory functions. This knowledge has created concerns regarding nonspecific B cell depletional therapy because of the potential to paradoxically augment immune responses. Recent studies now indicate that PCs have immune functions beyond immunoglobulin synthesis. Evidence for a new role for PCs as potent regulatory cells (via IL‐10 and IL‐35 production) is discussed including the implications for PC‐targeted therapies currently being developed for clinical transplantation.